Effects of δ‐tocotrienol on ochratoxin A—induced nephrotoxicity in rats. Issue 11 (18th May 2018) - Damiano, Sara; Navas, Luigi; Lombari, Patrizia; Montagnaro, Serena; Forte, Iris M.; Giordano, Antonio; Florio, Salvatore; Ciarcia, Roberto
Abstract : Ochratoxin A (OTA), is a natural contaminant of the food chain worldwide involved in the development of different type of cancers in animals and humans. Several studies suggested that oxidative damage might contribute to increase the cytotoxicity and carcinogenicity capabilities of OTA. The aim of this study was to evaluate the possible protective effect of δ‐tocotrienol (Delta), a natural form of vitamin E, against OTA‐induced nephrotoxicity. Male Sprague–Dawley rats were treated with OTA and/or Delta by gavage for 14 days. Our results shown that OTA treatment induced the increase of reactive oxigen species production correlated to a strong reduction of Glomerular Filtration Rate (GFR) and absoluted fluid reabsorption (Jv) with conseguent significant increase in blood pressure. Consistent, we noted in the kidney of rats treated with OTA, an increase in malondialdheyde and dihydroethidium production and a reduction of the activity of the catalase, superoxide dismutase, and glutathione peroxidase. Conversly, in the rat group subjected to the concomitant treatment OTA plus Delta, we observed the restored effect, compared the OTA treatment group, on blood pressure, GFR, Jv, and all activities of renal antioxidant enzymes. Finally, as far as concern the tissue damage induced by OTA and measured evaluating fibronectin protein levels, we observed that in OTA plus Delta group this effect is not restored. Our findings releval that a mechanism underlying the renal toxicity induced by OTA is the oxidative stress and provide a new rationale to use a Delta in order to protect, at least in part, against OTA‐induced nephrotoxicity. Abstract : Our findings releval that a mechanism underlying the renal toxicity induced by OTA is the oxidative stress and provide a new rationale to use a Delta in order to protect, at least in part, against OTA‐induced nephrotoxicity.